Surgical remotion of a cysticercotic granuloma responsible for refractory seizures : a case report. - Hasan, Md. Shariful; Basri, Hamidon; Lim, Poh Hin; Stanslas, Johnson (Medknow Publications, 2011)
BACKGROUND: Neurocysticercosis is the most common parasitic infestation of the central nervous system and an important cause of acquired epilepsy. Although endemic in developing countries, with an increased immigration from the endemic regions, it is also seen progressively in other parts of the world. Hence, there is an increased need for awareness of neurocysticercosis in the non-endemic areas. CASE DESCRIPTION: The case described here is of a 13-year-old girl who presented with refractory seizures. She had been on antiepileptic medication and had also received anti-parasitic treatment for neurocysticercosis. Surgical intervention was recommended because the seizures were resistant to treatment and also because the diagnosis could not be clearly established. Following surgery, the seizures have been under control and the patient has been doing well. CONCLUSION: Neurocysticercosis can be a potential cause of refractory seizure even in non-endemic countries. Some cases may be difficult to diagnose. Clinical presentation of seizure and brain imaging should be given priority over blood investigations for diagnosing neurocysticercosis and advanced neurosurgical intervention can be considered in suitable cases for better outcome.